Template attack on SPA and FA resistant implementation of Montgomery ladder. Issue 5 (1st September 2016) - Chakraborty, Abhishek; Bhattacharya, Sarani; Dixit, Tanu Hari; Rebeiro, Chester; Mukhopadhyay, Debdeep
Abstract : Hardware implementations of the well‐known Rivest–Shamir–Adleman (RSA) algorithm have been shown to be vulnerable to power and fault analysis (FA) attacks. To implement protected designs of RSA‐Chinese remainder theorem in embedded devices, like smart cards or RFIDs, the one needs to find solutions which require less computations as well as incurs low storage overheads. One such efficient scheme was proposed by Joye et al . in CHES'02 and it was claimed to be secure against both simple power analysis (SPA) and FA attacks. In this study, the authors demonstrate a template attack (TA) against Joye's countermeasure and show that the scheme can be broken with a low number of power traces. In addition, the authors report the experimental results of the proposed attack against an implementation of Joye's scheme on a Xilinx Microblaze soft‐core processor of SASEBO‐W standard side‐channel analysis board. The authors used least squares support vector machine (LS‐SVM) based binary classifiers to analyse the collected power traces. The authors also describe the potential threat posed by cache timing attacks on Joye's ladder in presence of a concurrently running spy process and outline a probable countermeasure to the posed attacks.